2020
DOI: 10.3389/fcvm.2020.583289
|View full text |Cite
|
Sign up to set email alerts
|

Use of Extracorporeal Membrane Oxygenation After Congenital Heart Disease Repair: A Systematic Review and Meta-Analysis

Abstract: Introduction: Extracorporeal membrane oxygenation (ECMO) has been widely used to treat cardiopulmonary failure in patients with congenital heart defects (CHD) postoperatively. A meta-analysis is performed for outcomes of postoperative CHD patients on ECMO. Methods: Electronic databases, including PubMed, EMbase, and Cochrane Library CENTRAL were searched systematically from January 1990 to June 2020 for literature which reported the outcomes of postoperative CHD cases on ECMO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 62 publications
2
16
0
1
Order By: Relevance
“… 33 A discrepancy between our pooled short‐term mortality of 45.6% and the above‐mentioned mortalities may be explained in part by the variance of patient selection and various VA‐ECMO managements without harmonized guidelines. Consistent with previous data, 39 , 47 , 48 , 49 , 50 , 51 in our subgroup analysis by diseases, the short‐term mortality of CHD and AFM were 51.5% and 21.6%, respectively. The significant difference ( P <0.001) suggested that patients with AFM had more favorable outcome than CHD.…”
Section: Discussionsupporting
confidence: 93%
“… 33 A discrepancy between our pooled short‐term mortality of 45.6% and the above‐mentioned mortalities may be explained in part by the variance of patient selection and various VA‐ECMO managements without harmonized guidelines. Consistent with previous data, 39 , 47 , 48 , 49 , 50 , 51 in our subgroup analysis by diseases, the short‐term mortality of CHD and AFM were 51.5% and 21.6%, respectively. The significant difference ( P <0.001) suggested that patients with AFM had more favorable outcome than CHD.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, significant advances in perioperative support to critically ill infants and children with congenital heart defects have been achieved with readily available and improved extracorporeal membrane oxygenation techniques. Expanded knowledge of extracorporeal membrane oxygenation indications and timing, cannulations strategies, anticoagulation management, extracorporeal membrane oxygenation circuit assessment and optimal flow rates have allowed clinicians to provide improved cardio-circulatory support and mitigate patient complications (33)(34)(35).…”
Section: Review Methodsmentioning
confidence: 99%
“…[22][23][24] A recent meta-analysis investigating outcomes of patients undergoing ECMO following congenital heart surgeries by Wu and colleagues found an estimated in-hospital mortality as high as 57%, and bleeding was the most common complication in 47%. 25 The pooled overall incidence of neurological events and renal failure was 47% and 39%, respectively. Consistent with the literature, our investigation demonstrated that the incidence of patients who required intra-or postoperative ECMO due to cardiopulmonary compromise was 3.8%.…”
Section: In-hospital Morbiditymentioning
confidence: 97%